Grade 10 Students’ Online Learning Readiness and e-Learning Engagement in a Science High School during Pandemic - Tabang, Merly P.; Caballes, Dennis G. (International Journal of Humanities and Education Development (IJHED), 2022)
Every area of the government faced enormous hurdles as a result of the COVID-19 outbreak. For the Department of Education, this meant using a different teaching modality to continue the students' education. Online learning, where students and teachers interact virtually and use Google Classroom as the learning management system (LMS), is one of the learning modes used during the pandemic. This study examined how prepared Grade 10 students of Puerto Princesa City National Science High School were for online learning and how engaged they were in it throughout the pandemic. According to the study's findings, the majority of students are prepared for online learning in terms of expectations, preferred methods of learning, and technological aptitude. On the other side, students must develop their capacity for initiative in their own learning and be provided with the necessary hardware and software to support their studies. Additionally, the students' grades indicate proficient to advanced level of e-learning engagement. Results also showed that there is no significant relationship between students’ online learning readiness and students' e-learning engagement in science subject during the pandemic. This implies that regardless of their readiness in online learning, students are capable of handling their tasks and get high grades